Hippocampal blood–brain barrier of methamphetamine self‐administering HIV‐1 transgenic rats. (27th August 2020) - Ohene‐Nyako, Michael; Persons, Amanda L.; Napier, T. Celeste
Abstract: Combined antiretroviral therapy for HIV infection reduces plasma viral load and prolongs life. However, the brain is a viral reservoir, and pathologies such as cognitive decline and blood–brain barrier (BBB) disruption persist. Methamphetamine abuse is prevalent among HIV‐infected individuals. Methamphetamine and HIV toxic proteins can disrupt the BBB, but it is unclear if there exists a common pathway by which HIV proteins and methamphetamine induce BBB damage. Also unknown are the BBB effects imposed by chronic exposure to HIV proteins in the comorbid context of chronic methamphetamine abuse. To evaluate these scenarios, we trained HIV‐1 transgenic (Tg) and non‐Tg rats to self‐administer methamphetamine using a 21‐day paradigm that produced an equivalency dose range at the low end of the amounts self‐titrated by humans. Markers of BBB integrity were measured for the hippocampus, a brain region involved in cognitive function. Outcomes revealed that tight junction proteins, claudin‐5 and occludin, were reduced in Tg rats independent of methamphetamine, and this co‐occurred with increased levels of lipopolysaccharide, albumin (indicating barrier breakdown) and matrix metalloproteinase‐9 (MMP‐9; indicating barrier matrix disruption); reductions in GFAP (indicating astrocytic dysfunction); and microglial activation (indicating inflammation). Evaluations of markers for two signaling pathways that regulate MMP‐9 transcription, NF‐κB and ERK/∆FosB revealed an overall genotype effect for NF‐κB. Methamphetamine did not alter measurements from Tg rats, but in non‐Tg rats, methamphetamine reduced occludin and GFAP, and increased MMP‐9 and NF‐κB. Study outcomes suggest that BBB dysregulation resulting from chronic exposure to HIV‐1 proteins or methamphetamine both involve NF‐κB/MMP‐9. Abstract : HIV proteins and methamphetamine cause blood‐brain barrier breakdown. Data obtained from this study suggests that the HIV‐ and/or methamphetamine‐induced blood‐brain barrier breakdown co‐occurs with an increase in inflammatory mediators that converge on MMP‐9, an extracellular matrix‐degrading enzyme implicated in blood‐brain barrier breakdown.